The boy who cried vampire : a graphic novel - Harper, Benjamin (Far out fables., 2018)
In this graphic version of the classic fable, Ion is a boy in a little town in Transylvania who loves to play tricks on the other villagers, so when a real vampire appears at his window nobody responds to his cries for help, and it looks like the final trick is on Ion--maybe.